100 ways to motivate others : how great leaders can produce insane results without driving people crazy - Chandler, Steve, 1944- (Career Press, 2008)
100 Ways to Motivate Others is the culmination of many years of successful leadership coaching and training by best-selling author Steve Chandler and attorney Scott Richardson. Chandler and Richardson have crafted a vital, user-friendly, inspirational guide for executives, managers, and professionals, as well as those aspiring to reach their level.